2015
DOI: 10.1210/en.2014-1874
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Ligand 20: A Signal for Leukocyte Recruitment During Human Ovulation?

Abstract: Ovulation is one of the cornerstones of female fertility. Disruption of the ovulatory process results in infertility, which affects approximately 10% of couples. Using a unique model in which the dominant follicle is collected across the periovulatory period in women, we have identified a leukocyte chemoattractant, chemokine ligand 20 (CCL20), in the human ovary. CCL20 mRNA is massively induced after an in vivo human chorionic gonadotropin (hCG) stimulus in granulosa (>10 000-fold) and theca (>4000-fold) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The cells were acclimated in culture as described previously (23) and then treated with or without hCG (1 IU/mL). The levels of P4 in conditioned media were increased by hCG compared with controls [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were acclimated in culture as described previously (23) and then treated with or without hCG (1 IU/mL). The levels of P4 in conditioned media were increased by hCG compared with controls [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that hGLC from IVF patients can respond to hCG after preincubation for 6 days (23). Indeed, these cells increased the production of P4 and PGE 2 /F 2a in response to hCG in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the preovulatory follicle contains inflammatory cytokines, such as IL-1, IL-2, IL-6, TNF-a, granulocyte-macrophage colony-stimulating factor (GM-CSF), and macrophage colony-stimulating factor (M-CSF) [180][181][182][183][184][185]. The LH surge produces chemokines that can attract various immune cells, such as neutrophils, monocytes, macrophages, NK cells, B cells, and T cells [186][187][188][189][190][191]. Neutrophils produce cytotoxic peptides and proteases, which can degrade the follicular wall [192,193].…”
Section: Ovulationmentioning
confidence: 99%
“…Among these leukocytes are neutrophils, monocytes, natural killer (NK) cells, dendritic cells (DCs), B cells, and T cells and for some of them, a critical role in the ovulation process has been proven (49,50). Notably, hCG also augments CCL20 expression in the ovaries and thereby stimulates a CCL20-driven leukocyte influx (51). Most likely, this function is attributed to the p-hCG isoform ( Figure 1A).…”
Section: Beneficial Role Of Hcg In Pregnancy and In Art-is The Immunementioning
confidence: 99%